Traduction télécollaborative en contexte pandémique : le cas de la BD ivoirienne Aya de Yopougon cotraduite en coréen - Jeanmaire Guillaume; 김대영 (통번역학연구, 25(1), 2021)
Like many of our colleagues, we have come to reconsider our methods as a result of the 2020 pandemic. It has also led us to rediscover the potential of telecollaboration solutions in translation programs. Among young students of different origins and languages, we sought to adjust our practices through oral online presentations, supplemented by written feedback from the class, on an open-editor. We thus optimized student engagement, eased by the distance and the synchronous mode of our video-conferencing courses. To captivate our audience, we chose an Ivorian comic book: "Aya de Yopougon." The graphics provided context that allowed our learners to better understand the plot, and it facilitated their access to cultural implications, which favored the co-translation of this comic. Collaborative written contributions have not only made it possible to bridge the distance between us, but also to increase solutions and fruitful creativity. During the confinement of the first semester, these written exchanges between pairs strengthened their engagement from afar. It was delicate to expect a sufficient level of Korean language from Mandarin-speaking students, and have them translate into Hangul (translation in B). Although the main focus of our class and of this article remains the translations conducted towards Korean language, thanks to our Chinese skills, we took the opportunity to translate that same comic work in Mandarin, in the prospect of a double commercial publication that really motivated them. KCI Citation Count: 0